Anomalously Broad Diffuse Interstellar Bands and Excited CH+ Absorption in the Spectrum of Herschel 36. Issue Volume 9:Issue S297(2013) (21st February 2014) - York, D. G.; Dahlstrom, J.; Welty, D. E.; Oka, T.; Hobbs, L. M.; Johnson, S.; Friedman, S. D.; Jiang, Z.; Rachford, B. L.; Snow, T. P.; Sherman, R.; Sonnentrucker, P.
Abstract: Anomalously broad diffuse interstellar bands (DIBs) at 5780.5, 5797.1, 6196.0, and 6613.6 Å are found in absorption along the line of sight to Herschel 36, an O star system next to the bright Hourglass nebula of the Hii region Messier 8. Excited lines of CH and CH + are seen as well. We show that the region is very compact and itemize other anomalies of the gas. An infrared-bright star within 400 AU is noted. The combination of these effects produces anomalous DIBs, interpreted by Oka et al . (2013, see also this volume) as being caused predominantly by infrared pumping of rotational levels of relatively small molecules.